2024
DOI: 10.1126/scitranslmed.adi7558
|View full text |Cite
|
Sign up to set email alerts
|

An anti-mycobacterial conjugated oligoelectrolyte effective against Mycobacterium abscessus

Kaixi Zhang,
Jakkarin Limwongyut,
Alex S. Moreland
et al.

Abstract: Infections caused by nontuberculous mycobacteria have increased more than 50% in the past two decades and more than doubled in the elderly population. Mycobacterium abscessus (Mab), one of the most prevalent of these rapidly growing species, is intrinsically resistant to numerous antibiotics. Current standard-of-care treatments are not satisfactory, with high failure rate and notable adverse effects. We report here a potent anti-Mab compound from the flexible molecular framework afforde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Yet, this fact highlights the limitation that reinfection remains unavoidable even after MABC eradication through adjunctive lung resection. Recent studies have reported immune or metabolic alterations related to the pathogenesis of NTM-PD [ 23–25 ]. Nevertheless, no decisive measures to prevent reinfection have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this fact highlights the limitation that reinfection remains unavoidable even after MABC eradication through adjunctive lung resection. Recent studies have reported immune or metabolic alterations related to the pathogenesis of NTM-PD [ 23–25 ]. Nevertheless, no decisive measures to prevent reinfection have been reported.…”
Section: Discussionmentioning
confidence: 99%